Breast Cancer Dormancy: Understanding ER+ Breast Cancer Dormancy Using Bioinspired Synthetic Matrices for Long‐Term 3D Culture and Insights into Late Recurrence (Adv. Biosys. 9/2020). Issue 9 (3rd September 2020) - Ovadia, Elisa M.; Pradhan, Lina; Sawicki, Lisa A.; Cowart, Julie E.; Huber, Rebecca E.; Polson, Shawn W.; Chen, Chuming; van Golen, Kenneth L.; Ross, Karen E.; Wu, Cathy H.; Kloxin, April M.
Abstract : In article number 2000119, April M. Kloxin and co‐workers establish a 3D human breast cancer dormancy model that captures key biophysical and biochemical properties of common metastatic microenvironments for late recurrence. The studies with this model demonstrate how matrix density and cell type impact cell dormancy versus proliferation and suggests autophagy as a survival mechanism of dormant ER+ breast cancer cells.